2013
DOI: 10.33477/bs.v2i2.372
|View full text |Cite
|
Sign up to set email alerts
|

ISOLAI DAN PENGUKURAN AKTIVITAS ENZIM BROMELIN DARI EKSTRAK KASAR BATANG NANAS (Ananas comosus) PADA VARIASI pH

Abstract: Penelitian ini bertujuan untuk mengisolasi enzim bromelin dari batang nanas (Ananas comosus) dan mengukur protein dan aktivitas enzim bromelin dengan substrat gelatin pada variasi pH. Hasil penelitian menunjukkan kadar protein tertinggi pada pengendapan dengan amonium sulfat 60% yaitu sebesar 37,785 µg/ml dan pH optimum aktivitas enzim bromelin yaitu pada pH 6,0 dengan nilai aktivitas 1,021 unit/gram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…According to Table 2, the highest enzyme activity was obtained at pH 6, as the activity increased with the increasing pH up to 6 and then decreased. It was previously reported that measurements of bromelain activity at pH 4.0 to 8.0 showed the highest activity at pH 6 [27], and a temperature of 50 • C and pH 6.0 were used in the hydrolysis process [28]. The results of this study showed that the bromelain enzyme conditions with the highest enzyme activity were at a temperature of 50 • C and pH 6.0, with an enzyme activity of 0.21 U/mL.…”
Section: Bromelain Activity At Various Ph Values and Temperaturessupporting
confidence: 49%
“…According to Table 2, the highest enzyme activity was obtained at pH 6, as the activity increased with the increasing pH up to 6 and then decreased. It was previously reported that measurements of bromelain activity at pH 4.0 to 8.0 showed the highest activity at pH 6 [27], and a temperature of 50 • C and pH 6.0 were used in the hydrolysis process [28]. The results of this study showed that the bromelain enzyme conditions with the highest enzyme activity were at a temperature of 50 • C and pH 6.0, with an enzyme activity of 0.21 U/mL.…”
Section: Bromelain Activity At Various Ph Values and Temperaturessupporting
confidence: 49%
“…Pineapple skin as waste can be extracted and used in tenderization by soaking old laying hens. Pineapple skin contains the enzyme bromelain with optimum activity at a temperature of 650C and a pH of 6.5 [21], [22]. Some other literature states that the optimal temperature of the bromelain enzyme is 40 0 C-60 0 C [23]- [25].…”
Section: Introductionmentioning
confidence: 99%